Cardiac defects, morbidity and mortality in patients affected by RASopathies. CARNET study results. (15th October 2017) - Calcagni, Giulio; Limongelli, Giuseppe; D'Ambrosio, Angelo; Gesualdo, Francesco; Digilio, M. Cristina; Baban, Anwar; Albanese, Sonia B.; Versacci, Paolo; De Luca, Enrica; Ferrero, Giovanni B.; Baldassarre, Giuseppina; Agnoletti, Gabriella; et al.
Abstract: Background: RASopathies are developmental disease caused by mutations in genes encoding for signal transducers of the RAS-MAPK cascade. The aim of the present study was to provide a comprehensive description of morbidity and mortality in patients with molecularly confirmed RASopathy. Methods: A multicentric, observational, retrospective study was conducted in seven European cardiac centres participating to theCA rdiacR asopathyNET work (CARNET). Clinical records of 371 patients with confirmed molecular diagnosis of RASopathy were reviewed. Mortality was described as crude mortality, cumulative survival and restricted estimated mean survival. Multivariable regression analysis was used to assess the impact of mutated genes on number of interventions and overall prognosis. Results: Cardiac defects occurred in 80.3% of cases, almost half of them underwent at least one intervention. Overall, crude mortality was 0.29/100 patients-year. Cumulative survival was 98.8%, 98.2%, 97.7%, 94.3%, at 1, 5, 10, and 20 years, respectively. Restricted estimated mean survival at 20 years follow-up was 19.6 years. Ten patients died (2.7% of the entire cohort; 3.4% of patients with cardiac defect). Patients with hypertrophic cardiomyopathy (HCM) and age < 2 years or young adults, as well as subjects with biventricular obstruction and PTPN11 mutations had a higher risk of cardiac death. Conclusions: The risk of intervention was higher in individuals with Noonan syndrome and pulmonary stenosis carrying PTPN11 mutations. Overall, mortality was relatively low, even though the specific association between HCM, biventricular outflow tract obstructions and PTPN11 mutations appeared to be associated with early mortality, including immediate post-operative events and sudden death.